Can tandem alternative splicing and evasion of premature termination codon surveillance contribute to attenuated Peutz–Jeghers syndrome?. Issue 10 (10th August 2022) - Gazzaz, Nour; Frost, F. Graeme; Alderman, Emily; Richmond, Phillip A.; Dalmann, Joshua; Lin, Susan; Salman, Areesha; Del Bel, Kate L.; Lehman, Anna; Turvey, Stuart E.; Boerkoel, Cornelius F.; Cherukuri, Praveen F.
Abstract: Alternative use of short distance tandem sites such as NAGNn AG are a common mechanism of alternative splicing; however, single nucleotide variants are rarely reported as likely to generate or to disrupt tandem splice sites. We identify a pathogenic intron 5 S TK11 variant (NM_000455.4:c.[735‐6A>G];[=]) segregating with the mucocutaneous features but not the hamartomatous polyps of Peutz–Jeghers syndrome in two individuals. By RNAseq analysis of peripheral blood mRNA, this variant was shown to generate a novel and preferentially used tandem proximal splice acceptor (AAG TGAAG ). The variant transcript (NM_000455.4:c.734_734 + 1insTGAAG), which encodes a frameshift (p.[Tyr246Glufs*43]) constituted 36%–43% of STK11 transcripts suggesting partial escape from nonsense mediated mRNA decay and translation of a truncated protein. A review of the ClinVar database identified other similar variants. We suggest that nucleotide changes creating or disrupting tandem alternative splice sites are a pertinent disease mechanism and require contextualization for clinical reporting. Additionally, we hypothesize that some pathogenic STK11 variants cause an attenuated phenotype.